The implementation of a blended education system at the Foreign Language Department of the University of El Salvador, for students in 4th and 5th year of Licenciatura en Lenguas Modernas, Especialidad en Francés e Inglés and, Licenciatura en Idioma Inglés Opción Enseñanza - Acosta Aguilar, Marlene Isabel; Aguilar Villalobos, Dina Keren; Cáceres Velásquez, Luz Margarita; Maldonado Mejía, Carlos Xavier; Mendizábal Arévalo, Odir Alexander; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2013)
The following work aims to understand the importance of the implementation of Blended Learning at Foreign Language Department at University of El Salvador, in order to help students of 4th and 5th year of the Licenciatura en Lenguas Modernas, Especialidad en Francés e Inglés and of the Licenciatura en Idioma Inglés, Opción Enseñanza that struggle with schedule issues or living in remote areas among others.
Anexos: instrumentos de la investigación.
Tesis -- (Licenciatura en Lenguas Modernas especialidad Francés e Inglés) -- Universidad de El Salvador, San Salvador, 2013
Referencias : hoja 88
La tesis está en formato digital.
Keywords: Lenguaje y lenguas -- Enseñanza; Planes de estudio